Provoked by Provocation, Human virtue and Telos, and the Intersection of Loneliness, Connection, and Technology: A Response to Brian Patrick Green’s “Emerging Technologies as Provocations for Theology and Ethics” - Molhoek, Braden (Theology and science, 2026)
This is a response to Brian Patrick Green's 2023 Russell Family Fellowship Conference Paper. I first explore Green's usage of “provocation.” Then in addressing his argument about transhumanism, I ask whether virtue can help us define sufficient change for a new form of humanity. Finally, I address Green's discussion of loneliness and connection. In a finite and imperfect world where no one is owed relationality, is technology an incomplete solution where some form of connection is better than no connection? Is the pursuit of AGI an example of humans yearning to not be alone in this world.